An Intelligent-Based Multiplicative Actuator Fault Estimation and Accommodation of Nonlinear Cooperative Systems - Salimifard, M.; Talebi, H.A. (2018 IEEE Conference on Control Technology and Applications (CCTA), 2018)
This paper is concerned with the fault-tolerant cooperative control of nonlinear Multi-Agent Systems (MASs) subject to multiplicative actuator faults. The model of the underlying leader-following MAS contains Lipschitz-type nonlinearities and external disturbances. In order to accomplish consensus tracking while simultaneous actuator faults may occur in some of the followers, an active fault-tolerant controller composed of online fault estimation and accommodation schemes is proposed. To obtain real-time information of the unknown time-varying fault functions, an observer-based fuzzy wavelet neural network is developed in each follower. Then, based on the estimated faults, an accommodation scheme is introduced to compensate the effects of faults. To illustrate the effectiveness of the proposed distributed fault-tolerant control approach, simulation results on a group of rotary-wing air vehicles are provided.